DETERITORIJALIZACIJA/RETERITORIJALIZACIJA I NOMADSKI IDENTITET U DJELIMA POSTJUGOSLAVENSKIH AUTORA - Doris Pandžić (Philological Studies, 2019)
This article presents already existing theories of nomadism by Felix Guattari, Gilles Deleuze and Vilém Flusser, explains the terminology used in these theories and applies it in the analysis of literary works of post-Yugoslav writers. Reassess the identification of nomadism and cosmopolitanism. Nomadism as a philosophy advocates the non-defining – by place, time and identity. Literary works were analyzed and compared: Скриена камера by Lidija Dimkovska, Снегот во Казабланка by Kica Bardžiovska-Kolbe, Čefurji raus! by Goran Vojnović, Nebesa v robidah by Nataša Kramberger, Snežni čovek by David Albahari and Muzej bezuvjetne predaje by Dubravka Ugrešić. After analysis, it was concluded that the said literary works could be classified as nomadic literature, which extracts that works from the framework of individual national literatures.